Formulasi Sabun Cair Cuci Tangan dan Uji Aktivitas Bakteri Staphylococcus aureus dari Ekstrak Daun Kelor (Moringa oleifera Lam.) - Waris, Dinda Izzatul; Yanti, Silfera Indra; Okzelia, Sari Defi; Amirulah, Fajar (Universitas Hamzanwadi, 2023)
Soap is what can be used to wash hands so as to avoid bacteria that can cause diseases such as acne and boils. One of the natural ingredients in making soap is Moringa leaves. Moringa leaves are one of the plants that have antibacterial properties, Staphylococcus aureus bacteria are bacteria that can cause infectious diseases such as acne and boils. The purpose of this study was to formulate hand washing liquid soap from Moringa leaf extract (Moringa oliefera Lam.), to evaluate the antibacterial activity of the preparation against Staphylococcus aureus. Moringa extract was obtained by maceration method. Furthermore, phytochemical screening was carried out, then formulated into soap preparations at concentrations of 20% (F1), 25% (F2), and 30% (F3). The preparations were evaluated and tested for activity against Staphylococcus aureus. Based on the results of the study, the yield of ethanol extract of Moringa leaves was 32.35% and contained secondary metabolites such as alkaloids, flavonoids, saponins and tannins. Moringa leaf ethanol extract soap formula met the requirements of all test parameters including pH test, irritation test, specific gravity test, and organoleptic test. The results of the antibacterial activity test gave an inhibition zone of 20.2 mm, 21.5 mm, and 23.2 mm, respectively. For F1, F2 and F3 against Staphylcoccus aureus.